Real-world efficacy and safety of lenvatinib: data from a compassionate use in the treatment of radioactive iodine-refractory differentiated thyroid cancer patients in Italy. (September 2019) - Locati, L.D.; Piovesan, A.; Durante, C.; Bregni, M.; Castagna, M.G.; Zovato, S.; Giusti, M.; Ibrahim, T.; Puxeddu, E.; Fedele, G.; Pellegriti, G.; Rinaldi, G.; et al.
Abstract: Background: Lenvatinib is a multi-kinase inhibitor approved for patients with radioactive iodine (RAI)–resistant differentiated thyroid cancer (DTC). Before the drug approval from the Italian National Regulatory Agency, a compassionate use programme has been run in Italy. This retrospective study aimed to analyse data from the first series of patients treated with lenvatinib in Italy. Methods: The primary aim was to assess the response rate (RR) and progression-free survival (PFS). Secondary end-points include overall survival (OS) and toxicity data. Results: From November 2014 to September 2016, 94 patients were treated in 16 Italian sites. Seventeen percent of patients had one or more comorbidities, hypertension being the most common (60%). Ninety-eight percent of patients were treated by surgery, followed by RAI in 98% of cases. Sixty-four percent of patients received a previous systemic treatment. Lenvatinib was started at 24 mg in 64 subjects. Partial response and stable disease were observed in 36% and in 41% of subjects, respectively; progression was recorded in 14% of patients. Drug-related side-effects were common; the most common were fatigue (13.6%) and hypertension (11.6%). Overall, median PFS and OS were 10.8 months (95% confidence interval [CI], 7.7–12.6) and 23.8 months (95% CI, 19.7–25.0) respectively. Conclusion: Lenvatinib is active and safe in unselected, RAI-refractory, progressive DTC patients in real-life setting. RR and PFS seem to be less favourable than those observed in the SELECT trial, likely due to a negative selection that included heavily pretreated patients or with poor performance status. Highlights: Patients with metastatic differentiated thyroid cancer (DTC) have poor survival rate. Lenvatinib improved clinical outcomes in patient with metastatic radioactive iodine-refractory DTC. Lenvatinib is active and safe, even in a real-life patient population. Older patients show survival benefit from lenvatinib, without safety concern.